Case Report: Dental treatment for an oboist: Post-trauma prosthetic rehabilitation and evaluation of musical performance - Hattori, Mariko; Patzelt, Sebastian B. M.; Itoh, Michiichiro; Sumita, Yuka I.; Wakabayashi, Noriyuki (Frontiers in Psychology, 2023)
Introduction The condition of teeth and function of the oral organs are important when playing wind or brass instruments. Although there are some reports on dental treatment for musicians, few studies have investigated their acoustic performance following treatment. This report describes the prosthodontic rehabilitation provided for an oboist who had lost a tooth as a result of trauma and includes an evaluation of her subsequent musical performance using acoustic analyses. Case Description The patient was a 63-year-old professional oboe player who fractured the upper and lower alveolar bone and avulsed the upper right central incisor during a fall due to epileptic seizure. While the alveolar fracture was healing, she sought maxillofacial rehabilitation for the missing tooth to maintain her ability to play the oboe. Her rehabilitation consisted of a provisional removable prosthesis with an acrylic base and clasps followed by a fixed implant prosthesis. A recording of her musical performance was objectively analyzed at each stage of treatment. Rhythm analysis confirmed the stability of notes played rapidly. Her performance dynamics were analyzed by psychoacoustic measurements. Her satisfaction with the prosthesis was assessed by a self-reported questionnaire. The results of the acoustic evaluation helped to adjust the provisional prosthesis so that it was suitable for playing the oboe and the final prosthesis was designed accordingly. Conclusion Prosthetic dental treatment for this patient included both subjective and objective evaluations that helped to ensure that she could continue playing the oboe at her previous performance level.